Cytogenetic Analysis and Clinical Phenotype of Primary Amenorrhea in Indonesian Patients - Aisha Balkhar Ali; Rita Indriyati; Tri Indah Winarni; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2018)
Background: Primary amenorrhea (PA) is a symptom that can be caused by different disorders such as gonadal, endocrinal, physiological and genetic disorders. Aim of study: This study provided the clinical and cytogenetic profiles of Indonesian primary amenorrhea patients and introduced clinical criteria of those patients with their karyotype results using score system. Methods: A retrospective descriptive study of 79 PA patients, whom referred to Cytogenetic and Molecular unit Center for Biomedical Research (CEBIOR), Faculty of Medicine Diponegoro University. We made a scoring system consisted of 4 scores, all patients had been distributed to match the scores according to their clinical criterias and then confirmed with the karyotype results. Results: The karyotype results of 79 patients of PA revealed 55 (69.6%) patients with female karyotype 46,XX; 6 (7.6%) patients with male karyotype 46,XY; 8(10.1%) patients with monosomy X; 3 (3.8%) patients with 45,X/46,XX; 3 (3.8%) patients with Isochromosome 45 X/46, X,i(Xq). Mosaicism with Y constitution 45,X/46,XY was seen in 2 (2.5%) patients; marker chromosome 45,X/46,X+mar (2%) in 1 patient (1.3%); and chromosome 1 and X translocation 46,XX,t(1;X)(p34;q25) detected in 1(1.3%) patient. Scoring system results showed that all patients with normal karyotype (46,XX/46,XY) were matched with score 1 and 2 while 17 patients with chromosomal abnormalities were matched with score 3 and 4, only 1 patient with mosaic Turner syndrome 45,X(10%)/46,XX(90%) matched score 1. Conclusion: Turner syndrome was the most common cause of primary amenorrhea which attests the importance of cytogenetic analysis for diagnosis of primary amenorrhea patients. The scoring system needs further validated for measuring reliability and validity.